Is Postural Control Different in Boys and Girls? Comparison Between Sex - Jessica Caroliny de Jesus Neves; Aryane Karoline Vital Souza; Dirce Shizuko Fujisawa (Universidade de São Paulo, 2021)
ABSTRACT The purpose of this study was to compare the postural control between eight-year-old boys and girls, considering the nutritional classification and level of physical activity. This was a cross-sectional study, with a sample of 346 participants, classified by the WHO AnthroPlus software, evaluated on the force platform and the Questionnaire Physical Activity for Children. The results demonstrated that girls showed lower values in relation to the opposite sex (p<0.001), in the center of pressure area (COP) (girls: 11.88 vs boys: 15.86cm2), Antero-posterior Amplitude (girl: 5.40 vs boy: 6.05cm), Medial-lateral Amplitude (girl: 3.97 vs boy: 4.40cm), Antero-posterior velocity (girl: 3.98 vs boy: 4.94cm/s), Medial-lateral velocity (girl: 3.98 vs boy: 4.59cm/s), Antero-posterior frequency (girl: 0.70 vs boy: 0.84Hz). Physical activity was associated with male sex (p=0.001; X2=11.195; odds ratio=0.372). In relation to the center of pressure of sedentary children, girls showed better postural control (p<0.001), but when we analyzed the center of pressure of both sexes who were active there was no statistically significant difference (p=0.112). The Z score of both sexes presented no difference in the center of pressure area (p=0.809 and p=0.785 respectively). Girls showed better postural control, while boys are more active; when both sexes performed physical activity COP area was similar. Therefore, special care should be taken when assessing postural control in boys and girls due to their differences in test performance and stage of development. As for interventions, exercise should be considered for better performance of the COP.